The Impact of Natural Resources: Survey of Recent Quantitative Evidence. Issue 2 (1st February 2017) - Van Der Ploeg, Frederick; Poelhekke, Steven
A bstract: The cross-country empirical evidence for the natural resource curse is ample, but unfortunately fraught with econometric difficulties. A recent wave of studies on measuring the impact of natural resource windfalls on the economy exploits novel datasets such as giant oil discoveries to identify effects of windfalls, uses natural experiments and within-country econometric analysis, and estimates local impacts. These studies offer more hope in the search of quantitative evidence.